Intellectual Property Disputes before the General Court of the European Union: Procedure and Experience Drawn from Handling Lithuanian Cases* - Ūkelytė, Renata (Teisė, 2024)
The article presents the particular procedure before the General Court of the European Union, i.e. the specific rules applicable in case of actions brought against the decisions of the European Union Intellectual Property Office (EUIPO) set out in the Rules of Procedure of the General Court complemented by the Practice Rules for the Implementation of the Rules of Procedure (last amended 30 November 2022).In addition, the article covers the procedural particularities of intellectual property cases resulting from the status of the other party in the procedure before the EUIPO, the rules of determining the language of the case, the absence of a second exchange of pleadings as well as other matters.The author analyses the procedural aspect of cases examined during the twenty years of Lithuania’s membership in the EU trade mark protection system.The article presents a study of the experience drawn by the Lithuanian lawyers in the field of intellectual property before the General Court and aims at providing intellectual property litigation experts with a relevant overview of the recent developments.